2018
DOI: 10.1111/sum.12418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and liming on macropore networks derived from X‐ray tomography images of a silty clay soil

Abstract: Soil structure influences water infiltration, aeration and root growth and, thereby, also the conditions for sustainable crop production. Our objective was to quantify the effects of different soil management methods and land uses on the topsoil structure of a silty clay soil. We sampled 32 intact soil columns (18 cm high, 12.7 cm diameter) from an experimental silty clay field with four treatments: conventional tillage (CT), conventional tillage followed by liming (CTL), reduced tillage (RT) and unfertilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…This, and the significantly lower CNO 3 N-Q slope than in the three other cropping systems, confirmed findings in adjacent experimental plots of significantly low NO 3 N leaching from fallow (Svanbäck et al 2014). At the same time, there was relatively high PP transport from the experimental plots under fallow, possibly because there were more vertically oriented macropores in fallow soil than in ploughed soil and the macropores were also better connected (Hellner et al 2018). In general, high variability in turbidity relative to Q for fallow (CV T /CT Q ) was observed in the present study.…”
Section: Concentrations and Leaching Under Altered Managementsupporting
confidence: 82%
“…This, and the significantly lower CNO 3 N-Q slope than in the three other cropping systems, confirmed findings in adjacent experimental plots of significantly low NO 3 N leaching from fallow (Svanbäck et al 2014). At the same time, there was relatively high PP transport from the experimental plots under fallow, possibly because there were more vertically oriented macropores in fallow soil than in ploughed soil and the macropores were also better connected (Hellner et al 2018). In general, high variability in turbidity relative to Q for fallow (CV T /CT Q ) was observed in the present study.…”
Section: Concentrations and Leaching Under Altered Managementsupporting
confidence: 82%
“…The six columns of soil from different land uses (forest, grassland and arable land) and soil depths (3-8 and 15-20 cm) are presented in Figs 1 and 2 in the form of 3D visualiza-tions of macropores in the soil. According to literature, the formation of smaller macropores is influenced by freezing and thawing, or the wetting and drying processes occurring in the soil (Hellner et al, 2018;Luo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we calculated the joint histogram for all 95 calibrated 3‐D images (see Figure ) and a joint‐threshold grayscale value of 10,171 was determined by the minimum method (Tsai, ). As was also done by Hellner et al (), we applied this threshold value to all gray‐scale‐calibrated images to obtain binary images depicting the X‐ray resolvable pores. Beckers et al () found that a similar global segmentation method performed as well as local approaches that are more demanding in terms of time and computational resources.…”
Section: Methodsmentioning
confidence: 99%